Jerzy Grotowski. - Slowiak, James (Routledge performance practitioners., 2018)
"Master director, teacher, and theorist, Jerzy Grotowski's work extended well beyond the conventional limits of performance. Now revised and reissued, this book combines:? an overview of Grotowski's life and the distinct phases of his work? an analysis of his key ideas? a consideration of his role as director of the renowned Polish Laboratory Theatre? a series of practical exercises offering an introduction to the principles underlying Grotowski's working methods. As a first step towards critical understanding, and an initial exploration before going on to further, primary research, Routledge Performance Practitioners offer unbeatable value for today's student."--Provided by publisher.